2017
DOI: 10.1088/1751-8121/aa5af3
|View full text |Cite
|
Sign up to set email alerts
|

The distribution of first hitting times of randomwalks on Erdős–Rényi networks

Abstract: Analytical results for the distribution of first hitting times of random walks on Erdős–Rényi networks are presented. Starting from a random initial node, a random walker hops between adjacent nodes until it hits a node which it has already visited before. At this point, the path terminates. The path length, namely the number of steps, d, pursued by the random walker from the initial node up to its termination is called the first hitting time or the first intersection length. Using recursion equations, we obta… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
32
0
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
6

Relationship

4
2

Authors

Journals

citations
Cited by 14 publications
(37 citation statements)
references
References 47 publications
4
32
0
1
Order By: Relevance
“…The distribution of last hitting times of SAWs on a directed ER network, obtained from Eq. (13), is also shown (dashed-dotted line). As expected, the last hitting times are significantly longer than the first hitting times on the same network.…”
Section: Summary and Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The distribution of last hitting times of SAWs on a directed ER network, obtained from Eq. (13), is also shown (dashed-dotted line). As expected, the last hitting times are significantly longer than the first hitting times on the same network.…”
Section: Summary and Discussionmentioning
confidence: 99%
“…For comparison we also present the corresponding distribution of RWs on an undirected ER network (dashed line) with the same value of c (based on Ref. [13]). It is found that the first hitting times of RWs on directed ER networks are much longer than those of 28).…”
Section: Summary and Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…For networks with an exponential component in the degree distribution as described in Eq. (22), the degree distribution conditioned on the finite components takes the form…”
Section: The Degree Distribution On the Giant Componentmentioning
confidence: 99%
“…It would help to obtain results pertaining only to the giant component of such systems, without the contributions from finite components which often amount to trivial contaminations or (unwanted) distortions of results. Examples that come to mind are localization phenomena in sparse matrix spectra [17,18] (where finite components of a random graph support eigenvectors that are trivially localized), properties of random walks [19][20][21][22] (where a random walker chosen to start a walk on one of the finite components will never be able to explore an appreciable fraction of the entire network), or the spread of diseases or cascading failures [23][24][25][26][27][28] (where an initial failure or initial infection occurring on a finite component will never lead to a global system failure or the outbreak of an epidemic). Component-size distributions in the percolation problem on complex networks [27,29] will likewise contain a component originating from clusters that were finite, before nodes or edges were randomly removed from the network.…”
Section: Introductionmentioning
confidence: 99%